Who killed Karkare? : the real face of terrorism in India - Mushrif, S. M. (New Delhi : Pharos Media & Pub., 2009)
Presentation of the view that Intelligence Bureau is creating false propaganda about Islamic terrorism in India and hiding the communal activities of the Hindu organizations.
Keywords: Karkare, Hemant, -- 1954-2008 -- Assassination; India. -- Intelligence Bureau; Terrorism -- India; Communalism -- India